2016
DOI: 10.1099/ijsem.0.000674
|View full text |Cite
|
Sign up to set email alerts
|

Bradyrhizobium vignae sp. nov., a nitrogen-fixing symbiont isolated from effective nodules of Vigna and Arachis

Abstract: Twenty one strains of symbiotic bacteria from root nodules of local races of cowpea (Vigna unguiculata), Bambara groundnut (Vigna subterranea) and peanuts (Arachis hypogaea) grown on subsistence farmers' fields in the Kavango region of Namibia, were previously characterized as a novel group within the genus Bradyrhizobium. To verify their taxonomic position, the strains were further analysed using a polyphasic approach. 16S rRNA gene sequences were most similar to Bradyrhizobium manausense BR 3351 T , with Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 27 publications
1
29
1
Order By: Relevance
“…Nowadays, the suggested threshold for species delineation for the genus Bradyrhizobium using five concatenated genes is 97 % NI [22]. Several phylogenetic studies have suggested a minimum of four [6, 12], or even three [8] concatenated housekeeping genes in the MLSA, and a considerable number of Bradyrhizobium species have been described using four genes and an NI value of 97 % as the threshold for species delineation [2, 13, 33, 35, 36]. In our study, both sets of genes on the MLSA presented NI for the new groups compared with the most related species far below 97 %; the only exception was of group GII.III, which shared from 97 to 97.3 % NI with B.…”
Section: Phylogenymentioning
confidence: 60%
“…Nowadays, the suggested threshold for species delineation for the genus Bradyrhizobium using five concatenated genes is 97 % NI [22]. Several phylogenetic studies have suggested a minimum of four [6, 12], or even three [8] concatenated housekeeping genes in the MLSA, and a considerable number of Bradyrhizobium species have been described using four genes and an NI value of 97 % as the threshold for species delineation [2, 13, 33, 35, 36]. In our study, both sets of genes on the MLSA presented NI for the new groups compared with the most related species far below 97 %; the only exception was of group GII.III, which shared from 97 to 97.3 % NI with B.…”
Section: Phylogenymentioning
confidence: 60%
“…Consistent with the results obtained with the 16S rDNA gene sequence analysis in this study, the sequence data of nifH and three housekeeping genes ( atpD , recA and glnII ) of the nodule occupants of the five Bambara groundnut landraces also aligned with diverse species of Bradyrhizobium . Single gene phylogenetic analysis showed that some of the nodule bacteria in this study were related to Bradyrhizobium vignae , which nodulates Vigna subterranea , Vigna unguiculata , Arachis hypogaea and Lablab purpureus [ 45 ]. In the phylogenetic trees constructed from sequences of atpD , recA and glnII genes, some monophyletic groups were identified which showed no close relationship with any reference strains.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gronemeyer et al . [ 45 , 51 52 ] showed that Bradyrhizobium subterraneum , Bradyrhizobium kavangense and Bradyrhizobium vignae (all of African origin) are responsible for the nodulation of Bambara groundnut. However, from the phylogenetic analysis of individual and concatenated genes in this study, there were many unknown Bradyrhizobium species from Ghanaian and South African soils that nodulated Bambara groundnut, and are still waiting to be properly described.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis also revealed the presence of a new subgroup of Bradyrhizobium, forming a symbiotic association with groundnut. Recent studies identified novel genospecies of Bradyrhizobium involved in nodulation [21,25]. Well-supported groups, obtained based on the intergenic spacer (IGS) sequences, were also retrieved using the nodC gene, suggesting nodC and IGS regions are generally transmitted vertically.…”
Section: Diversity Among Bacterial Strains Associated With Groundnut Rnsmentioning
confidence: 91%